2012
DOI: 10.1097/sla.0b013e31824b7697
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Medical Outcomes After Tailored Surgery for Pain Due to Chronic Pancreatitis

Abstract: Operative intervention for painful CP, tailored to anatomical abnormalities, results in excellent to fair long-term pain relief, but approximately 10% of patients do not respond. QoL scores remained slightly compromised. High preoperative pain levels, suggested through daily opioid use and high numbers of endoscopic procedures, are associated with less favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 47 publications
2
52
0
1
Order By: Relevance
“…This is in accordance with previous studies, 39,40 and is further confirmed by a recent systematic review reporting a rate of 39% for newonset DM after distal pancreatectomy. 41 The relatively enriched distribution of islets in distal pancreas and the additional surgical resection based on pre-existing fibroinflammatory destruction of pancreatic parenchyma offer possible explanations.…”
Section: Discussionsupporting
confidence: 79%
“…This is in accordance with previous studies, 39,40 and is further confirmed by a recent systematic review reporting a rate of 39% for newonset DM after distal pancreatectomy. 41 The relatively enriched distribution of islets in distal pancreas and the additional surgical resection based on pre-existing fibroinflammatory destruction of pancreatic parenchyma offer possible explanations.…”
Section: Discussionsupporting
confidence: 79%
“…The patients who most benefit from PD have low preopera tive pain levels, suggested by the lack of daily opioid use, few endoscopic procedures and have dilated ducts (8mm or greater). 50 If pain persists, celiac plexus block and pregabalin, or a complete pancreatectomy and islet cell autotransplanta tion should be considered. 51 Although low, patients with pancreatitis have an increased risk of developing pancreatic cancer.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…A Roux-en-Y jejunal limb is sutured side-to-side to the pancreas [75]. The procedure is associated with low morbidity and mortality rates (about 1%) [20,21]. Immediate and lasting pain relief is reported in 80% (range 42-100%) of the patients with a follow-up of 62 (range 15-110) months [20].…”
Section: Surgical Therapymentioning
confidence: 99%
“…Recently, an expert center published their results of a large cohort of patients with CP who underwent surgery for CP. After a median period of 40 months (10-90th percentile; 12-132 months) after start of pain complaints and after a median of 2 (range 0-29) endoscopic procedures, patients were referred for surgery [21]. Other indications for surgery are a suspicion of neoplasm and local complications of adjacent organs, such as duodenal or common bile duct stenosis, pseudoaneurysm or erosion of the large vessels, large pancreatic pseudocysts, and internal pancreatic fistula.…”
Section: Surgical Therapymentioning
confidence: 99%
See 1 more Smart Citation